Comparison of Covid-19 Control Policies Between Indonesia and Australia Based on the Perspective of Policy Capacity Theory - Ardian Rizki Serda Ginata; Pryanka Pandu; Nurul Handayani; Putu Aditya Ferdian Ariawantara (Jurnal Borneo Administrator, 2022)
The Covid-19 pandemic scrutinized the readiness and challenges of a country's control policies in the Asia Pacific region. This article aims to compare the policy capacity for Covid-19 control between the governments of Indonesia and Australia from the perspective of policy capacity theory. This article uses a qualitative case study method with data collection techniques for literature studies, online investigations, and data analysis. The two countries have something in common in implementing public health policies related to Covid-19, but the authors found different results. Based on the analysis using the theory of policy capacity, from the aspect of analytical capacity, it was found that the Indonesian Government was slow to respond to the Covid-19 pandemic. In contrast, the Australian Government carried out mandatory continuity of the Covid-19 policy. Then in terms of operational capacity, Indonesia still has minimum capacity and resources compared to those Australia. In terms of political capacity, the Government of Indonesia has lost public trust due to policy inconsistencies in controlling Covid-19. Meanwhile, the Australian Government can build public trust with transparent information disclosure. As a country with a large area and a high population in the face of Covid-19, it is necessary to strengthen policy capacity starting with practical policy design, leadership skills, good coordination between cross levels of government, and political legitimacy and public trust